2014
DOI: 10.1021/nl502612m
|View full text |Cite
|
Sign up to set email alerts
|

Materials Processing Routes to Trap-Free Halide Perovskites

Abstract: Photovoltaic devices based on lead iodide perovskite films have seen rapid advancements, recently achieving an impressive 17.9% certified solar power conversion efficiency. Reports have consistently emphasized that the specific choice of growth conditions and chemical precursors is central to achieving superior performance from these materials; yet the roles and mechanisms underlying the selection of materials processing route is poorly understood. Here we show that films grown under iodine-rich conditions are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
702
5
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 704 publications
(764 citation statements)
references
References 47 publications
41
702
5
2
Order By: Relevance
“…Because ARTICLE structural defects are known to play a crucial role in perovskite optical properties, 20,65,66 this weak PL intensity could be attributed to surface defects. In agreement with this idea, CH 3 NH 3 PbI 3 wires and rods made in the presence of the surface passivating n-octylammonium cation have a higher PL QYs of 1.7À1.4%, and their PL lifetimes inversely correlate with their aspect and surface-to-volume ratios (Table 1, see also Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Because ARTICLE structural defects are known to play a crucial role in perovskite optical properties, 20,65,66 this weak PL intensity could be attributed to surface defects. In agreement with this idea, CH 3 NH 3 PbI 3 wires and rods made in the presence of the surface passivating n-octylammonium cation have a higher PL QYs of 1.7À1.4%, and their PL lifetimes inversely correlate with their aspect and surface-to-volume ratios (Table 1, see also Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[25][26][27][28][29] This is responsible for its bipolar conducting property and long carrier diffusion length (owing to absence of charge trapping centers). Because the M 3+ ion in A 2 M + M 3+ X VII 6 adopts the Sb 3+ /Bi 3+ that have the same electron configuration (ns 2 ) with Sn 2+ /Pb 2+ , it is reasonably conjectured that similar defect-tolerant feature might be to some extent at play here.…”
Section: Combinatory Materials Screening Of Potentially Highphotovoltmentioning
confidence: 99%
“…In contrast, iodine-poor conditions obtained through the use of lead acetate as the precursor result in fewer defects and a longer charge diffusion length. [42] In a comparative study with other lead precursors, Aldibaja et al showed that films derived from lead acetate resulted in the most homogeneous perovskite films, and a photovoltaic performance comparable to the state-of-the-art. [43] Zhang et al further optimized the use of lead acetate as a precursor and showed that ultrasmooth and pinhole-free perovskite films could be obtained with this method.…”
Section: Crystallization From Lead-acetate Precursorsmentioning
confidence: 99%